Antibodies to Both Ro52 and Ro60 for Identifying Sjögren's Syndrome Patients Best Suited for Clinical Trials of Disease‐Modifying Therapies. Issue 9 (10th June 2022) - Armağan, Berkan; Robinson, Susan A.; Bazoberry, Adriana; Perin, Jamie; Grader‐Beck, Thomas; Akpek, Esen K.; Kim, Jean; Baer, Alan N.
Abstract : Objective: To assess anti‐Ro52 and anti‐Ro60 serologic profiles as markers of clinically relevant phenotypic subsets of patients with Sjögren's syndrome (SS). Methods: From a cohort of 839 consecutive patients with suspected or established SS seen in our multidisciplinary SS center, we compared the association of key phenotypic features in 390 patients who fulfilled SS classification criteria and in the parent cohort, stratifed by the presence of both anti‐Ro60 and anti‐Ro52, anti‐Ro60 alone, and anti‐Ro52 alone. Results: The SS cohort included 227 patients (58%) with both anti‐Ro60 and anti‐Ro52, 65 (17%) with anti‐Ro60 alone, 58 (15%) with anti‐Ro52 alone, and 40 (10%) with neither antibody. Those with both anti‐Ro60 and anti‐Ro52 had a significantly increased prevalence of abnormal ocular surface staining, focal lymphocytic sialadenitis with focus score ≥1, antinuclear antibody ≥1:320, anti‐SSB/La, rheumatoid factor, and IgG ≥15.6 gm/liter ( P < 0.0016 for all). The groups with isolated anti‐Ro52 and anti‐Ro60 were equivalent to each other in their phenotypic associations, except for rheumatoid factor, which was higher in the anti‐Ro52 alone group. The associations of these Ro antibody serologic profiles were similar in the parent cohort, except for additional associations with salivary gland enlargement and parotid gland ultrasound score. Conclusion: SS patients with both anti‐Ro60 and anti‐Ro52 antibodies are distinguished by a higher prevalence of markers of B‐cell hyperactivity and glandular inflammation. Antibody reactivity to both Ro60 and Ro52 may thus serve as an important inclusion criterion for SS patients in clinical trials where the therapeutic agent targets pathways mediating these pathogenic abnormalities.